Classification of modules of dimension n and multiplicity 1 over the Weyl algebra A_n - Bavula, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
Modules of the Gelfand - Kirillov dimension n and the multiplicity 1 over the Weyl algebra A_n are classified.